Construction of Ni‐Co‐Fe Hydr(oxy)oxide@Ni‐Co Layered Double Hydroxide Yolk‐Shelled Microrods for Enhanced Oxygen Evolution. Issue 49 (9th November 2022) - Niu, Qian; Yang, Min; Luan, Deyan; Li, Nian Wu; Yu, Le; Lou, Xiong Wen (David)
Abstract: The exploration of earth‐abundant and efficient electrocatalysts toward the oxygen evolution reaction (OER) is critical for sustainable energy storage and conversion devices. In this work, we report a self‐engaged strategy to fabricate a yolk‐shelled OER electrocatalyst. Starting with a metal–organic framework, Co‐Fe layered double hydroxide (LDH)@zeolitic imidazolate framework‐67 (ZIF‐67) yolk‐shelled structures are formed in one step. Afterwards, these ZIF‐67 building blocks are transformed into Ni‐Co LDH nanocages to form the Ni‐Co‐Fe hydr(oxy)oxide@Ni‐Co LDH yolk‐shelled microrods (NiCoFe‐HO@NiCo‐LDH YSMRs) through an ion‐exchange reaction. Owing to the structural and compositional merits, the NiCoFe‐HO@NiCo‐LDH YSMR electrocatalyst exhibits an overpotential of 278 mV to reach the current density of 10 mA cm −2, a small Tafel slope of 49.7 mV dec −1, and good stability in alkaline media. Abstract : Ni‐Co‐Fe hydr(oxy)oxide@Ni‐Co layered double oxide yolk‐shelled microrods (NiCoFe‐HO@NiCo‐LDH YSMRs) are designed as an electrocatalyst for the oxygen evolution reaction (OER) through a two‐step conversion strategy. Owing to the enhanced mass transport of the structure and the modulated chemical environment of metal species, the obtained NiCoFe‐HO@NiCo‐LDH YSMRs demonstrate enhanced electrocatalytic activity for OER with good stability.